DA'WAH COMMUNICATION PATTERNS OF MUHAMMADIYAH BEJI IN DEVELOPMENT COMMUNITIES IN THE BEJI TIMUR VILLAGE, DEPOK - Sari, Raudia Kartika Sari; Fadlilah, Siti Nur (Jurnal Da'wah: Risalah Merintis, Da'wah Melanjutkan, 2023)
Research Objectives: To find out how the communication patterns of Da'wah Muhammadiyah in the Beji area in community development in the East Beji sub-district, Depok. Research Methods: Descriptive Qualitative Results: Based on the results of the research that Muhammadiyah in fostering the community in the East Beji Depok village uses a wheel pattern, a star pattern, and a chain pattern. These patterns can be seen in the programs and activities of Muhammadiyah Depok in the coaching process for the East Beji Depok community. The wheel pattern is applied to programs in the fields of Worship and Da'wah, namely a pattern that directs all information to individuals who occupy central positions, while the star pattern is applied to programs in the fields of education and social and community affairs, because all members can communicate with other members that allow optimal member participation. While the chain pattern is applied to programs in the education sector only where this pattern the members at the end can only communicate with one person, namely the teacher. The other patterns, namely the circle pattern, are not applied in the communication process of East Beji Muhammadiyah in coaching programs carried out by East Beji Muhammadiyah.